"There is no such thing as a straight woman": Queer female representations in South Asian graphic narratives. Issue 4 (2nd October 2018) - Bhadury, Poushali
ABSTRACT: This essay provides a brief overview of some recent Indian and Bangladeshi comics and graphic novels, whether print-based or online, which feature queer female characters. The essay contextualizes these texts with respect to the anti-LGBTQ+ legal climate in South Asian countries, but also places them within a larger trajectory of literary representations of queer (female) love in the Indian subcontinent. The texts under examination range from print graphic novels and indie comics anthologies in India to comic strips brought out by queer activists working for LGBTQ+education and advocacy in Bangladesh. Taken together, they offer diverse portrayals of female-centric love and desire that challenge hetero-patriarchal representations of desi women.